Letters from Baghdad [videorecording (DVD)] (PBS Distribution, 2018)
Gertrude Bell is sometimes called the female Lawrence of Arabia. Bell was an explorer, spy, archaeologist, and diplomat who helped shape the Middle East after World War I. Advisor to Winston Churchill and critic of colonial policies in Iraq, Bell was considered the most powerful woman in the British Empire. The film takes viewers into a past that is eerily current.